2018
DOI: 10.1016/j.rfe.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Over‐investment or risk mitigation? Corporate social responsibility in Asia‐Pacific, Europe, Japan, and the United States

Abstract: We study the relationship of corporate social responsibility (CSR) and the distribution of stock returns for an international sample. Firms with a high level of CSR generally exhibit superior stock price synchronicity in the markets of Europe, Japan, and the United States. In particular, we identify optimal levels of CSR to minimize idiosyncratic risk for each region. Moreover, CSR has a mitigating effect on crash risk in Europe and the United States. In contrast, firms from the Asia‐Pacific region display CSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 122 publications
(213 reference statements)
7
79
0
2
Order By: Relevance
“…Majority of the studies found a positive relationship between CSP and financial performance (Atan, Alam, Said, & Zamri, 2018;Godfrey et al, 2009;Velte, 2017). However, CSP may influence the financial performance negatively due to stakeholders' negative perception over high emphasise on CSP (Utz, 2018)…”
Section: Social Performance and Financial Performancementioning
confidence: 99%
“…Majority of the studies found a positive relationship between CSP and financial performance (Atan, Alam, Said, & Zamri, 2018;Godfrey et al, 2009;Velte, 2017). However, CSP may influence the financial performance negatively due to stakeholders' negative perception over high emphasise on CSP (Utz, 2018)…”
Section: Social Performance and Financial Performancementioning
confidence: 99%
“…One possible reason for the lack of consistent statistically significant changes in donations in this study is cultural or institutional. Utz [96] explained that companies in the Asia-Pacific regions tend to overinvest in CSR, unlike companies in the US, Europe, and Japan. His finding is that the higher the CSR of Asian companies, the greater the risk of the stock price crash, possibly due to the lower corporate governance.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We too hypothesize a nonlinear relationship between CSP and loan spreads, but we assume a different relationship from that of Bae et al [15]. Several studies find evidence that CSP has a mitigating effect on stock price crash risk [43] and on downside risk [44,45]. From a theoretical point of view, the previous literature argues that CSR investments can reduce a firm's risk exposure through insurance-like protection by generating moral capital among stakeholders.…”
Section: Do Csr Ratings Affect Loan Spreads?mentioning
confidence: 91%
“…In addition, we have already clarified (see Introduction) that the results provided by Bae et al [15] for the US market cannot be mechanically extended to other institutional contexts. In this respect, further confirmation comes from Utz [43], who examines the predictive power of CSP for both idiosyncratic risk and stock crash risk in an international sample and finds mixed results. In the Asia-Pacific sample, high CSP increases crash risk, in accordance with the overinvestment hypothesis.…”
Section: Do Csr Ratings Affect Loan Spreads?mentioning
confidence: 98%